Analysis Of Leverage, Liquidity, And Esg Disclosure On Financial Performance (A Study On Companies In The Food And Beverage Sub-Sector Listed On The Indonesia Stock Exchange In 2017-2021) - Aminah, Wiwin; Wahyuni, Dhian; Radhiyya, Zidny Robbie (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Financial performance is a report on the financial performance of a company over a specific period. This research analyzes the influence of leverage, liquidity, and ESG disclosure on the financial performance of companies in the food and beverage sub-sector in the Indonesian Stock Exchange for years 2017 through 2021. The sample selection in this study used purposive sampling technique, resulting in 15 companies with a span of 5 years, making a total of 75 samples in this study. This research employs a quantitative method, and it is a descriptive study. Used a method panel data regression. The results obtained through descriptive statistics and panel data testing using the common effect model indicate that leverage, liquidity, and ESG disclosure collectively impact financial performance. Specifically, leverage has a negative impact, liquidity has a positive impact, and ESG disclosure does not affect the financial performance of companies in the food and beverage sub-sector listed on the Indonesian Stock Exchange for yaers 2017 through 2021.